Identifying and Reflecting on Representations of Indigenous People and Peasants using Critical Multimodal Storytelling (2022)
ABSTRACT : This action-research aimed at identifying and reflecting on ideas, assumptions and generalities about Colombian indigenous communities and peasants using Multimodal Storytelling. It was conducted in a public school in Rionegro, Antioquia with 25 third graders. Action strategies included involvement and exploration of students’ ideas and assumptions about indigenous people and peasants. Data gathering instruments included teacher’s journal, questionnaires, students’ artefacts, and interviews. Findings referred to four cases-participants, including me; as follows: From Intransitive Thought to “I changed my Mind”, From Semi Transitive to “Knowing about Them Is Knowing more about History”, From Stereotypes to a Reflective Thought, and Me as the teacher from Semi Transitive Thought to Action as Part of the Reflective Thought.